MON-176 Discovery and Identification of Late Stage Selective Nonpeptide ACTH Antagonists for the Treatment of Cushing’s Disease, Ectopic ACTH Secreting Tumors, and Congenital Adrenal Hyperplasia - Kusnetzow, Ana Karin (J Endocr Soc, 2020)
Adrenocorticotropic hormone (ACTH) is an important modulator of steroidal hormone synthesis and secretion from the adrenal gland and its selective activity at the melanocortin type 2 receptor (MC2) dictates the synthesis and secretion of cortisol (corticosterone in rats). Excess ACTH action contribute to the pathophysiology of Cushing’s disease (CD), ectopic ACTH secreting tumors (EAS), and Congenital Adrenal Hyperplasia (CAH). Cushing’s disease results from a microadenoma derived from pituitary corticotrophic cells that secretes excess ACTH, whereas EAS arises from nonpituitary ACTH secreting tumors. Excess ACTH action at the adrenal gland and resulting hypercortisolemia presents in a myriad of symptoms that result in high morbidity. CAH results from inactivating mutations in steroid synthesis pathways, resulting in lack of cortisol and aldosterone production. Lack of negative feedback by cortisol at the level of the pituitary causes the over-secretion of ACTH, and overproduction of adrenal androgens, causing significant virilization and reduction in quality of life. We hypothesize that blocking ACTH action directly via a selective MC2 receptor antagonist may provide an important new therapeutic mechanism for these patients. To test this hypothesis, Crinetics launched an iterative medicinal chemistry program to identify potent and selective nonpeptide ACTH antagonists with pharmaceutical and safety characteristics suitable for evaluation in human clinical trials. Unlike most other G protein coupled receptors, MC2 requires the presence of an accessory protein (MRAP) for cell surface expression and recognition of ACTH. Using CHO-K cells stably expressing this MC2-MRAP complex, iterative optimization led to the discovery of multiple chemical classes of highly potent, nonpeptide MC2 receptor selective antagonist leads, which were then further optimized for drug-like characteristics. We identified multiple compounds that exhibit high potency for human and rat MC2 receptors (hMC2 K(b) <1 nM), while having no activity at the MC1, MC3, MC4, or MC5 receptors. Leading ACTH antagonists were also evaluated for drug like characteristics, including good stability in liver microsomes, lack of inhibition of cytochromes P450 and the hERG ion channel, and were shown to exhibit good exposure upon oral dosing in both rats and dogs. These ACTH antagonists acutely suppress corticosterone secretion in an ACTH-challenge model in rats. In a 7-day hypercortisolemia model in which rats receive an implanted minipump that continually secretes ACTH, corticosterone levels were decreased, and body weight loss and adrenal hypertrophy were prevented with ACTH antagonist treatment. The culmination of these studies has led to a subset of candidate molecules that are being evaluated in genotoxicity, safety pharmacology, and general toxicology studies to enable evaluation in human clinical trials.